Role of the Lymphotoxin/LIGHT System in the Development and Maintenance of Reticular Networks and Vasculature in Lymphoid Tissues - Lu, Theresa T.; Browning, Jeffrey L. (Frontiers in Immunology, 2014)
Lymphoid organs are meeting zones where lymphocytes come together and encounter antigens present in the blood and lymph or as delivered by cells migrating from the draining tissue bed. The exquisite efficiency of this process relies heavily on highly specialized anatomy to direct and position the various players. Gated entry and exit control access to these theaters and reticular networks and associated chemokines guide cells into the proper sections. Lymphoid tissues are remarkably plastic, being able to expand dramatically and then involute upon resolution of the danger. All of the reticular scaffolds and vascular and lymphatic components adapt accordingly. As such, this organ is a wonderful example of a physiologic remodeling process and is potentially a guide to study such elements in pathological settings such as fibrosis, chronic infection and tumor metastasis. The lymphotoxin/LIGHT axis delivers critical differentiation signals that direct and hone differentiation of both reticular networks and the vasculature. Considerable progress has been made recently in understanding the mesenchymal differentiation pathways leading to these specialized networks and in the remodeling that occurs in reactive lymph nodes. In this article we will review some new advances in the area in terms of developmental, differentiation and maintenance events mediated by this axis.